Enantioselective N‐Heterocyclic Carbene Catalysis that Exploits Imine Umpolung. Issue 12 (14th February 2019) - Fernando, Jared E. M.; Nakano, Yuji; Zhang, Changhe; Lupton, David W.
Abstract: The catalytic umpolung of imines remains an underdeveloped approach to reaction discovery. Herein we report an enantioselective aza‐Stetter reaction that proceeds via imine umpolung using N‐heterocyclic carbene catalysis. The reaction proceeds with high levels of enantioselectivity (all ≥96:4 er) and good generality (21 examples). Mechanistic studies are reported and are consistent with turnover‐limiting addition of the NHC to the imine. Abstract : Poles apart : Imine umpolung is an underdeveloped area of enantioselective catalysis. N‐Heterocyclic carbenes (NHCs) were used to catalyze an enantioselective aza‐Stetter reaction. In contrast to acyl umpolung with NHCs, this reaction requires highly nucleophilic catalysts. The reaction is highly enantioselective (all ≥96:4 er) and accepts various imines and 3‐methylenechroman‐2‐ones.